Caring ability of urban and rural family caregivers: association with overburden, stress and coping* - Siqueira, Fernanda Duarte; Girardon-Perlini, Nara Marilene Oliveira; Andolhe, Rafaela; Zanini, Roselaine Ruviaro; Santos, Evelyn Boeck dos; Dapper, Steffani Nikoli (Revista da Escola de Enfermagem da USP, 2021)
Objective: To correlate caring ability with overburden, stress and coping of urban and rural family caregivers of patients undergoing cancer treatment. Method: Cross-sectional study, carried out in a referral hospital for cancer treatment, with urban and rural caregivers who responded the following instruments: questionnaire of sociodemographic characterization of the caregiver and the care provided, Perceived Stress scale, Burden Interview scale and Brief COPE. Pearson's correlation test was used for statistical analysis, with a significance level ≤5%. Results: A total of 163 urban caregivers and 59 rural caregivers participated in the study. Between the caring ability and stress, a negative and moderate correlation was found in rural caregivers. In the relationship between the caring ability and the overburden, there was a statistically significant correlation in urban caregivers in the interpersonal relationship and perception of self-efficacy factor. Between coping and the caring ability, a positive and moderate correlation was identified in coping focused on the problem in the knowledge dimension in urban caregivers. Conclusion: Urban caregivers had greater intensity of overburden and coping focused on the problem in relation to the caring ability.